2022
DOI: 10.1002/adfm.202207966
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Annealing Budget of Metal Oxide Thin‐Film Transistors Prepared by an Aqueous Blade‐Coating Process

Abstract: Metal oxide (MO) semiconductors are widely used in electronic devices due to their high optical transmittance and promising electrical performance. This work describes the advancement toward an eco-friendly, streamlined method for preparing thin-film transistors (TFTs) via a pure water-solution bladecoating process with focus on a low thermal budget. Low temperature and rapid annealing of triple-coated indium oxide thin-film transistors (3C-TFTs) and indium oxide/zinc oxide/indium oxide thin-film transistors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 102 publications
1
6
0
Order By: Relevance
“…Post-thermal annealing (PTA) under an oxygen atmosphere has been also used to partially compensate for the oxygen losses from In 2 O 3 . 13,28 Ma and co-workers reported the positive influence of the PTA process on In 2 O 3 -TFTs, 29 which was also suggested earlier by Yeom et al 30 Note that postprocess annealing has been shown to improve the threshold voltage shift, 31 field-effect mobility, 32,33 and channel-to-source/drain metallization interface resistivity. 34−36 The effects of these aforementioned In 2 O 3 thermal treatments on the chemical and electronic structures of the adjacent layers and buried interfaces must also be considered seriously during optimization of the In 2 O 3 -based TFTs.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Post-thermal annealing (PTA) under an oxygen atmosphere has been also used to partially compensate for the oxygen losses from In 2 O 3 . 13,28 Ma and co-workers reported the positive influence of the PTA process on In 2 O 3 -TFTs, 29 which was also suggested earlier by Yeom et al 30 Note that postprocess annealing has been shown to improve the threshold voltage shift, 31 field-effect mobility, 32,33 and channel-to-source/drain metallization interface resistivity. 34−36 The effects of these aforementioned In 2 O 3 thermal treatments on the chemical and electronic structures of the adjacent layers and buried interfaces must also be considered seriously during optimization of the In 2 O 3 -based TFTs.…”
Section: Introductionsupporting
confidence: 57%
“…Post-thermal annealing (PTA) under an oxygen atmosphere has been also used to partially compensate for the oxygen losses from In 2 O 3 . , Ma and co-workers reported the positive influence of the PTA process on In 2 O 3 -TFTs, which was also suggested earlier by Yeom et al Note that postprocess annealing has been shown to improve the threshold voltage shift, field-effect mobility, , and channel-to-source/drain metallization interface resistivity. …”
Section: Introductionmentioning
confidence: 75%
“…To investigated the influence of Al dopant on oxygen defects of the films, the X-ray photoelectron spectroscopy (XPS) of IZO and IAZO films are executed, as shown in Figure 2(a) and Figure 2(b). The XPS O1s spectra is resolved into two peaks, OI peak at 530 eV and OII peak at 531 eV, and they represent the metal-oxygen bond and oxygen defects, respectively [8]. Table 1 lists area ratio of OI and OII peak, i.e., OI/(OI + OII) and OII/(OI + OII).…”
Section: Resultsmentioning
confidence: 99%
“…He et al demonstrated this by using electrohydrodynamic printing technology to prepare nanosilver temperature sensors [31]. However, the range of ink viscosity that could be used in this technology was limited, and the temperature resistance of the sensor was only 105 • C. The blade-coating process is not only cost-effective and has a brief preparation cycle [32] but also allows printing on cylindrical surface substrates with large curvatures. For example, Zhao et al demonstrated a platinum-platinum/rhodium thick film thermocouple using blade coating technology, showcasing the method's capability to print on curved surfaces [33].…”
Section: Introductionmentioning
confidence: 99%